2019
DOI: 10.3906/sag-1712-147
|View full text |Cite
|
Sign up to set email alerts
|

Determining the insulin secretion potential for certain specific G-protein coupled receptors in MIN6 pancreatic beta cells

Abstract: Background/aim: The polypeptide hormone insulin is essential for the maintenance of whole-body fuel homeostasis, and defects in insulin secretion and/or action are associated with the development of type 1 and type 2 diabetes. The aim of this study was to assess the role of some G-protein coupled receptors (GPCRs), GPR54, GPR56, and GPR75, and cannabinoid receptors CB1R and CB2R, in the regulation of pancreatic β-cell function. Materials and methods: Insulin secretion from mouse insulinoma β-cell line (MIN6) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Accordingly, RANTES/CCL5, through the activation of the CCRs, reduces glucose-stimulated GLP-1 secretion in the human enteroendocrine cell line NCI-H716 and in mice in vivo, resulting in impaired insulin secretion after glucose stimulation in mice [ 238 ]. On the other hand, via GPR75, RANTES/CCL5 stimulates insulin secretion from β-cell lines [ 239 ] and mouse and human pancreatic islets in vitro, and improves glucose tolerance in lean mice and a mouse model of hyperglycaemia and insulin resistance without changing insulin sensitivity [ 237 ]. Interestingly, it has been demonstrated that adiponectin can negatively regulate the expression of RANTES/CCL5 [ 240 ].…”
Section: Dysfunctional Adipose Tissue Secretome Affects β-Cell Functi...mentioning
confidence: 99%
“…Accordingly, RANTES/CCL5, through the activation of the CCRs, reduces glucose-stimulated GLP-1 secretion in the human enteroendocrine cell line NCI-H716 and in mice in vivo, resulting in impaired insulin secretion after glucose stimulation in mice [ 238 ]. On the other hand, via GPR75, RANTES/CCL5 stimulates insulin secretion from β-cell lines [ 239 ] and mouse and human pancreatic islets in vitro, and improves glucose tolerance in lean mice and a mouse model of hyperglycaemia and insulin resistance without changing insulin sensitivity [ 237 ]. Interestingly, it has been demonstrated that adiponectin can negatively regulate the expression of RANTES/CCL5 [ 240 ].…”
Section: Dysfunctional Adipose Tissue Secretome Affects β-Cell Functi...mentioning
confidence: 99%
“…GPR56 is the most abundantly expressed aGPCR in β cells of human and murine islets, indicating an important role in islet function. Moreover, insulin‐secreting MIN6 mouse insulinoma cells express high levels of GPR56 mRNA 66 . GPR56 mRNA expression in human islets is negatively correlated to β‐cell function and type 2 diabetes (T2D) risks.…”
Section: Physiological Role Of Gpr56mentioning
confidence: 99%
“…Moreover, insulin-secreting MIN6 mouse insulinoma cells express high levels of GPR56 mRNA. 66 GPR56 mRNA expression in human islets is negatively correlated to βcell function and type 2 diabetes (T2D) risks. Reduced GPR56 expression has been found in islets from T2D patients, db/db mice, and normal human islets chronically treated ex vivo in hyperglycaemic conditions.…”
Section: Physiological Role Of Gpr56 In Metabolismmentioning
confidence: 99%
“…No direct binding studies of CCL5 to GPR75 were documented in that study. Recent studies reported that pancreatic islets as well as beta cell lines express GPR75 and that CCL5 stimulates insulin secretion via PLC‐activated Ca 2+ influx in a GPR75‐dependent manner; however, they also did not document direct binding or interaction between GPR75 and CCL5 (Gencoglu et al, 2019; Liu et al, 2013). Importantly, the pairing of CCL5 and GPR75 could not be repeated in a β‐arrestin assay (Davenport et al, 2013; Dedoni et al, 2018; Southern et al, 2013).…”
Section: Introductionmentioning
confidence: 99%